A family of solution-processable macrocyclic and open-chain oligothiophenes with atropoisomeric scaffolds: structural and electronic features for potential energy applications. (15th August 2017) - Quartapelle Procopio, E.; Benincori, T.; Appoloni, G.; Mussini, P. R.; Arnaboldi, S.; Carbonera, C.; Cirilli, R.; Cominetti, A.; Longo, L.; Martinazzo, R.; Panigati, M.; Pò, R.
Abstract : Cyclic and linear inherently chiral oligothiophenes have been employed as donors in bulk heterojunction solar cells with fullerenes as acceptors. Abstract : FeCl3 oxidation of the racemate of C 2 symmetric, inherently chiral, sexithiophene monomer1 (2, 2′-bis(2, 2′-bithiophene-5-yl)-3, 3′-bithianaphthene) affords a mixture of cyclic oligomers, from the prevailing dimer to traces of the pentamer. The oligomers are constituted by mixtures of stereoisomers which are two for dimer2, four for trimer3 and six for tetramer4 . Cyclooligomers2 and3 could be separated by chromatography, while4 was synthesized by ring closure of open chain dimer2a, prepared in turn by controlled coupling of the anion of racemic1 . The optical properties of open-chain stereoisomer2a and tetramer4 have been compared with those of2 and3 respectively. The macrocyclic oligomers have been tested as donor materials in bulk heterojunction solar cell prototypes both as a crude mixture resulting from oxidation of1 and as a single oligomer. Theoretical calculations support the photophysical properties of these new materials.